URGENSI TATA KELOLA INOVASI PEREKAMAN DATA DAN DOKUMEN KEPENDUDUKAN - M. Husein Maruapey (Jurnal Governansi, 2019)
Managing innovation involves many complex activities from organizations, stakeholders, and knowledge. Innovation is essential in improving the efficiency of the public sector. So the importance of governance innovation will provide the consequences of any failure or success of the innovation itself. Governance innovation also reflects the managing innovation in a way that is innovative as one strategy innovation process, so that innovation can show results and benefits. The focus of this research is the investigation phenomenon of governance innovations data and documents civil registration record with innovative ways in Southeast Aceh Regency. Also comparative with some other local government do it. Methods of qualitative analysis with phenomenology are used to be able to explain and illustrate and identify how the phenomenon occurs. Data collection is done inductively, interview, discussion, observation, and participation. Data reduction do with descriptive between empirical and secondary data. Images, tables, symbols, and lines used to realities revealed. Triangulation is used to conclude carefully from empirical and secondary data. The results of this research finding, governance innovation are innovative should be supported by policies, aside from the leadership capability as the executor. Citizen participation, cooperation various sector also contributes to a positive endorsement. Innovation is also an immediate need at this time for delivering excellent public services and competitive by the government.Keywords: Innovation Governance, Innovative, Public Service, Government.